SITE 12: TANJUNG DATU-MALUDAM IMCA - Aazani, Mujahid; Cindy, Peter (WWF-Malaysia, 2024)
This MyIMCA site proposed connecting existing areas which include Tanjung Datu National Park, Samunsam Wildlife Sanctuary, Talang Satang National Park, Kuching Wetlands (RAMSAR), Gunung Santubong National Park, and Bako National Park.